Mendelian randomization and Bayesian model averaging of autoimmune diseases and Long COVID - Feng, Jieni; Chen, Jiankun; Li, Xiaoya; Ren, Xiaolei; Chen, Junxu; Li, Zuming; Wu, Yuan; Zhang, Zhongde; Yang, Rongyuan; Li, Jiqiang; Lu, Yue; Liu, Yuntao (Frontiers in Genetics, 2024)
Background: Following COVID-19, reports suggest Long COVID and autoimmune diseases (AIDs) in infected individuals. However, bidirectional causal effects between Long COVID and AIDs, which may help to prevent diseases, have not been fully investigated.Methods: Summary-level data from genome-wide association studies (GWAS) of Long COVID (N = 52615) and AIDs including inflammatory bowel disease (IBD) (N = 377277), Crohn's disease (CD) (N = 361508), ulcerative colitis (UC) (N = 376564), etc. were employed. Bidirectional causal effects were gauged between AIDs and Long COVID by exploiting Mendelian randomization (MR) and Bayesian model averaging (BMA).Results: The evidence of causal effects of IBD (OR = 1.06, 95% CI = 1.00-1.11, P = 3.13E-02), CD (OR = 1.10, 95% CI = 1.01-1.19, P = 2.21E-02) and UC (OR = 1.08, 95% CI = 1.03-1.13, P = 2.35E-03) on Long COVID was found. In MR-BMA, UC was estimated as the highest-ranked causal factor (MIP = 0.488, MACE = 0.035), followed by IBD and CD.Conclusions: This MR study found that IBD, CD and UC had causal effects on Long COVID, which suggests a necessity to screen high-risk populations.